2009
DOI: 10.1080/19397030903151296
|View full text |Cite
|
Sign up to set email alerts
|

Energy and temperature performance analysis of geothermal (ground source) heat pumps integrated with permeable pavement systems for urban run-off reuse

Abstract: Who helped me with undergraduate course preparations and discussed various important scholarly issues with me.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…As a result of the strong variability of the chosen pollutants, the standard deviations for suspended solids were 151.3 mg/L and 190.9 mg/L for the inflow water with and without additional pollutants (dog faeces), respectively. Gully pots on the roadside where sampling occurred linked the surface runoff the continuous inflow of solids into roadside gully pots leads to gradual silting and a high varying suspended and total solids content [13,18]. Similar observations were made for biological oxygen demand (especially with the addition of dog faeces, IN + P) and conductivity.…”
Section: Inflow Water Qualitysupporting
confidence: 65%
“…As a result of the strong variability of the chosen pollutants, the standard deviations for suspended solids were 151.3 mg/L and 190.9 mg/L for the inflow water with and without additional pollutants (dog faeces), respectively. Gully pots on the roadside where sampling occurred linked the surface runoff the continuous inflow of solids into roadside gully pots leads to gradual silting and a high varying suspended and total solids content [13,18]. Similar observations were made for biological oxygen demand (especially with the addition of dog faeces, IN + P) and conductivity.…”
Section: Inflow Water Qualitysupporting
confidence: 65%
“…The COP value was fairly stable at around 3 during the project period, which is higher than for other similar research demonstration projects in which GSHP and SUDS have been combined. For example, Tota-Maharaj et al [34] found COP values between 2.3 and 4.5 for their indoor rigs, and between 1.5 and 4.5 for their outdoor rigs, whereas Charlesworth et al [24] found a mean COP value of 1.8. The predominant reason for the higher COP values in this investigation is most likely the higher capacity of GSHP in the Climate Road, with 800 m of geothermal pipe heat exchangers, the continuous infiltration of water to the pipes and the depth of the GSHP pipes (0.5 and 1.0 m, respectively).…”
Section: Energy Productionmentioning
confidence: 99%
“…Rainwater harvesting using permeable pavements has enhanced the Sustainable Urban Drainage System techniques with energy applications before rainwater is reused, by introducing GSHP systems . Many researches have demonstrated the potential of integrating permeable pavements with GSHP and underground water storage to reduce runoff peaks, store water, treat pollutants, lower heat island effect, and harvest energy from the heated pavement. Tota‐Maharaj and Scholz presented effective application of ANN for analyzing the performance of combined permeable pavement and GSHP system.…”
Section: Technologies Of Energy Harvesting From Pavements and Roadwaysmentioning
confidence: 99%